ANALISIS KESALAHAN BAHASA DALAM PENGGUNAAN KATA PADA LIRIK LAGU ‘KALIH WELASKU’ DENNY CAKNAN - Nisha Agustina Wulandari; Bagus Wahyu Setyawan (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
Song is part of poetry literature whose depiction of the contents of the heart is sung and covered with music. Each song lyric has its own meaning for the creator. Like one of the famous songs entitled 'Kalih compassion' which was popularized by Denny Caknan which carries the theme of a love song. However, the part in the lyrics of the song has several spelling errors in the use of each word. Based on this background, the focus of this research is to contextually analyze every word in the lyrics of the song 'kalih compassion'. Contextual analysis is discourse analysis that relies on the internal aspects of discourse and everything that externally encompasses a discourse. The context of discourse can be broadly divided into language contexts and external language contexts. Then it is known; (1) Analysis of Errors in Writing Words in the Lyrics of the Song 'Kalih Welasku', (2) Contextual Analysis of the Lyrics of 'Kalih Welasku' using the Principle of Personal Interpretation. The method used is descriptive qualitative. Based on the analysis of the words in the lyrics of the song 'kalih welasku'. The focus of this research is the analysis of language errors with the primary data of the song Kalih Welasku and secondary data in the form of articles, scie ntific studies, or documents that have a correlation with the research object.   Keywords: songs, contextual analysis, language errors